Urinary metabolomics reveals kynurenine pathway perturbation in newborns with transposition of great arteries after surgical repair - Simonato, Manuela (Metabolomics, 2019)
INTRODUCTION: Transposition of the great arteries (TGA) is a cyanotic congenital heart defect that requires surgical correction, with the use of cardiopulmonary-bypass (CPB), usually within 3 weeks of life. The use of CPB in open heart surgery results in brain hypoperfusion and in a powerful systemic inflammatory response and oxidative stress. OBJECTIVE: We aimed to develop a novel untargeted metabolomics approach to detect early postoperative changes in metabolic profile following neonatal cardiac surgery. METHODS: We studied 14 TGA newborns with intact ventricular septum undergoing arterial switch operation with the use of CPB. Urine samples were collected preoperatively and at the end of the surgery and were analyzed using an untargeted metabolomics approach based on UHPLC-high resolution mass spectrometry. RESULTS: Since post surgery metabolic spectra were heavily contaminated by metabolites derived from administered drugs, we constructed a list of drugs used during surgery and their related metabolites retrieved from urine samples. This library was applied to our samples and 1255 drugs and drug metabolites were excluded from the analysis. Afterward, we detected over 39,000 unique compounds and 371 putatively annotated metabolites were different between pre and post-surgery samples. Among these metabolites, 13 were correctly annotated or identified. Metabolites linked to kynurenine pathway of tryptophan degradation displayed the highest fold change. CONCLUSIONS: This is the first report on metabolic response to cardiac surgery in TGA newborns. We developed an experimental design that allowed the identification of perturbed metabolic pathways and potential biomarkers of brain damage, limiting drugs interference in the analysis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11306-019-1605-3) contains supplementary material, which is available to authorized users.